Women and youth in agriculture - Lambrecht, Isabel B.; Mahrt, Kristi; Cho, Ame; Ei Win, Hnin (International Food Policy Research Institute, 2024)
Gendered social and cultural norms often strongly emphasize women’s roles as caregivers. Such norms may, in turn, contribute to gender patterns in economic activity, including agricultural activity. Meanwhile, youth are at a critical stage in their lives as they transition from being “dependent” household members to a more independent stage of life, with increasing caregiving and income-generating responsibilities. There may, therefore, be generational differences between youth and non-youth in terms of their contributions to economic activities—including the extent to which they are involved in one sector or another.